Wykorzystanie technologii zarządzania wiedzą oràz zarządzania projektem w projektach Six Sigma - Kania, Krzysztof (Knowledge and project management in Six Sigma projects, 2006)
Organizations try to improve their performance by improving key processes. They undertake many efforts to implement systems that support improving process quality in various fields of management. The article presents a short synthesis of a mutual influence of Knowledge Management, Project Management and Six Sigma approaches and investigates for synergic effects of putting in work those three approaches together.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 331-340